The Effect of Profitability, Board Size, Woman on Boards, and Political Connection on Financial Distress Conditions - Nawang Kalbuana; Muhamad Taqi; Lia Uzliawati; Dadan Ramdhani (Cogent Business & Management, 2022)
This research proves the consistency of Agency Theory as a solution to explain the role of the influence of profitability, board size, woman on board, which is divided into two, namely woman on board of commissioner and woman on board of directors, as well as political connections to financial distress. Panel data from these variables were obtained from companies listed in LQ-45 in 2017-2021 which were then analyzed with a quantitative approach through the regression analysis of Ordinary Least Squares, Fixed Effects, Random Effects, and Robust, which was carried out simultaneously. The results of this analysis have a higher level of accuracy compared to partial testing. The first finding explains that the Profitability Ratio has a negative effect on financial distress, the second finding explains that board size has a positive effect on financial distress, the third finding explains that woman on board of commissioner has no effects on financial distress, however, the fourth finding explains that woman on board of director has a positive effect on financial distress, while the fifth finding explains the political connection has no positive effect to financial distress. Panel data-based research through simultaneous testing can be considered for principals in appointing agents to manage the company. Simultaneous analysis of panel data is a new breakthrough in research testing with more detailed results.
Keywords: G02; G32; G34; M1; Z1; 650; agency theory; financial distress; Panel data; simultaneous testing